An electrochemical study of electroactive, ferrocene-terminated, self-assembled monolayers - Kinsella, Michael (Trinity College (Dublin, Ireland). School of Chemistry, 2008)
Nanoscience includes the study of objects and systems in which at least one dimension is 1-100 nm. At these sizes, nanosystems can exhibit interesting and useful physical behaviours based on quantum phenomena. An area of Nanoscience that has received particular attention over the past 10 years is the area of molecular electronics. The concept of molecular electronics is an enticing alternative to extend Moore's Law beyond the foreseen limits of small-scale conventional silicon integrated circuits. This area was first proposed by Mulliken and Szent-Gyorgi in 1940 however it was not until 1974 when Ratner and Aviram(1) proposed the possible production of a molecular rectifier that this area received particular attention. In the late 1990s Mark Reed and Jim Tour(2) succeeded in demonstrating molecular circuitry in the laboratory. They showed that a monolayer of about 1000 molecules exhibited the phenomenon of negative differential resistance (NDR) - a current-voltage characteristic that differs from the normal in certain special systems. This property leads to the possibility of a molecular 'memory' being developed. As a result, molecular electronics is currently a very active research field, sometimes marked by controversy since many fundamental questions concerning both theory and expenments are left open. Much controversy remains regarding the fundamental events governing electron transfer through single molecules. Self-assembled monolayers, in particular redox-active molecules, provide an ideal platform to study such processes. To this end my Ph.D. has concentrated on the properties of redox active molecules, the complete understanding of which is essential to the development of molecular electronics.
Keywords: Chemistry, Ph.D.; Ph.D. Trinity College Dublin